On passenger saturation flow in public transport doors. (August 2015) - Fernández, Rodrigo; Valencia, Alejandra; Seriani, Sebastian
Highlights: The concept of passenger saturation flow in public transport doors is defined. The same behaviour of vehicles at traffic signals was found in public transport doors. Passenger saturation flow could be measured with the Road Note 34 method of TRRL. Laboratory experiments showed that results depend on door width and platform height. Results are valuable for traffic engineering, transport modelling and policy. Abstract: In previous studies the authors have shown passengers' boarding and alighting times for the Transantiago system obtained at the Pedestrian Accessibility and Movement Environment Laboratory (PAMELA) of University College London. Following this line of research, the aim of this paper is to demonstrate the existence of pedestrian saturation flows in public transport doors and show some values of this variable under different conditions. The methodology to achieve this aim was real-scale experiments performed in both PAMELA and the Human Dynamics Laboratory at Universidad de los Andes in Santiago de Chile. Different groups of people getting off a mock-up of a public transport vehicle were recorded by means of video cameras. The videos were then visually processed to find values of passenger saturation flow according to door configurations. The variables studied were the vertical gap between the platform and the vehicle chassis and the width of the door. Results indicate that it is possible to define values of passenger saturation flows for different characteristics of public transport doors. These values proved to be statistically sensitive to both the vertical gap and the width of the door. In addition, results indicate that there seems to be both a vertical gap and a door width for which the flow of passenger reaches its optimum rate.